Spiritual Pedagogy in the Digital Learning Environment: Reconstructing Self-Esteem among Vulnerable Children - Alvina Rahmadani (Zamzami Scholar Publishing, 2026)
The transformation of the educational environment in the digital age requires a pedagogical approach that not only emphasizes cognitive aspects but also strengthens learners’ emotional and spiritual dimensions, especially for children who grow up without direct parental care. This study aims to analyze the role of spiritual pedagogy in strengthening the self-esteem of foster children through learning practices developed in the digital learning ecosystem at Kampung Anak Negeri Unit Pelaksana Teknis Daerah (UPTD) Wonorejo Surabaya, East Java. This study uses a qualitative approach with a phenomenological design to understand participants’ life experiences through in-depth interviews, participatory observation, and thematic analysis. The analytical framework is based on Carl Rogers’ humanistic psychology perspective, which emphasizes learner-centered instruction, empathy, and unconditional acceptance in the educational process. The results show that integrating spiritual reflection practices, dialogical mentoring, and digital media into learning interactions can strengthen positive self-concept, increase self-confidence, and help children develop emotional resilience when facing social and psychological challenges. These findings confirm that spiritual pedagogy, integrated into the digital learning environment, can serve as a holistic pedagogical framework for strengthening children’s character, psychological well-being, and identity development in contemporary education.